Role of caveolae in high glucose and TGF-β(1) induced fibronectin production in rat mesangial cells - Liu, Yuantao (Int J Clin Exp Pathol, 2014)
Accumulation of extracellular matrix (ECM) in glomerular mesangium correlates with loss of renal function in diabetic nephropathy. However, the mechanisms underlying are still incompletely known. In the present study, we explored the role of caveolae in ECM production in rat mesangial cells (MCs) stimulated by high glucose or transforming growth factor-β(1) (TGF-β(1)), and investigated the possible mechanisms. High glucose (HG) or TGF-β(1) significantly increased collagen-1 and fibronectin expression at both mRNA and protein levels in time- course dependent manners, and simultaneously induced caveolin-1 tyrosine phosphorylation. Disruption of caveolae with Methyl-β-cyclodextrin (β-MCD) prevented HG and TGF-β(1) induced caveolin-1 tyrosine phosphorylation, and attenuated fibronectin but not collagen-1 production. This effect of β-MCD on fibronectin production could be abolished by cholesterol, which restored HG and TGF-β(1) induced caveolin-1 tyrosine phosphorylation. In addition, HG and TGF-β(1) induced fibronectin production was attenuated by a caveolin-1 scaffold domain peptide. These findings indicate that mesangial cell caveolae regulate fibronectin production at least partly through caveolin-1 phosphorylation.